Interobserver Agreement for Endometrial Cancer Characteristics Evaluated on Biopsy Material. (2nd February 2012) - Nofech-Mozes, S.; Ismiil, N.; Dubé, V.; Saad, R. S.; Ghorab, Z.; Grin, A.; Ackerman, I.; Khalifa, M. A.
Abstract : A shift toward a disease-based therapy designed according to patterns of failure and likelihood of nodal involvement predicted by pathologic determinants has recently led to considering a selective approach to lymphadenectomy for endometrial cancer. Therefore, it became critical to examine reproducibility of diagnosing the key determinants of risk, on preoperative endometrial tissue samples as well as the concordance between preoperative and postresection specimens. Six gynaecologic pathologists assessed 105 consecutive endometrial biopsies originally reported as positive for endometrial cancer for cell type (endometrioid versus nonendometrioid), tumor grade (FIGO 3-tiered and 2-tiered), nuclear grade, and risk category (low risk defined as endometrioid histology, grade 1 + 2 and nuclear grade <3). Interrater agreement levels were substantial for identification of nonendometrioid histology (κ = 0.63; SE = 0.025), high tumor grade (κ = 0.64; SE = 0.025), and risk category (κ = 0.66; SE = 0.025). The overall agreement was fair for nuclear grade (κ = 0.21; SE = 0.025). There is agreement amongst pathologists in identifying high-risk pathologic determinants on endometrial cancer biopsies, and these highly correlate with postresection specimens. This is ascertainment prerequisite adaptation of the paradigm shift in surgical staging of patients with endometrial cancer.